Interruptions Reduce Performance across All Levels of Signal Detection When Estimations of Confidence are Highest. (September 2016) - Aguiar, Nathan; Zish, Kevin; McCurry, J. Malcolm; Trafton, J. Gregory
When people are highly confident in their memory of a particular event, it is likely that the accuracy of that memory is also high. However, research has shown that the relationship between confidence and memory accuracy changes under certain circumstances. Interruptions, for instance, have been shown to change this relationship (Zish, Hassanzadeh, McMurry, & Trafton, 2015). The present study sought to determine the response behavior associated with this change. Results indicated that the change in the relationship between memory and confidence is characterized by a decrease in the rate of hits and an increase in the rate of false alarms. Thus, interruptions disrupt the relationship between memory and confidence by reducing sensitivity across all levels of signal detection.